The Impact of Intellectual Capital on the Efficiency of Job Performance: An Applied Study on a Sample of Primary Healthcare Sector Centers in Fallujah (Journal of Economic Additions, 2025)
This study examines the impact of intellectual capital on job performance in Al-Fallujah Health Sector Centers. Using statistical tools (T-test, ANOVA, regression), it analyzed the link between knowledge, skills, innovation, and performance. A questionnaire was distributed to 200 employees classified by gender and education. Results show a positive relationship between intellectual capital and performance, with skills, knowledge, and innovation directly enhancing efficiency. Significant differences appeared between males and females, and across educational levels. The study highlights that continuous training and innovation strengthen intellectual capital, while education level strongly influences job performance.Jel Classification Codes: J24, I18, M12
Keywords: Intellectual capital, job performance, Fallujah health sector centers, statistical analysis, performance effectiveness